Changes in Whole Blood Polyamine Levels and Their Background in Age-Related Diseases and Healthy Longevity - Kuniyasu Soda (Biomedicines, 2023)
The relationship between polyamines and healthy longevity has received much attention in recent years. However, conducting research without understanding the properties of polyamines can lead to unexpected pitfalls. The most fundamental consideration in conducting polyamine studies is that bovine serum used for cell culture contains bovine serum amine oxidase. Bovine serum amine oxidase, which is not inactivated by heat treatment, breaks down spermine and spermidine to produce the highly toxic aldehyde acrolein, which causes cell damage and activates autophagy. However, no such enzyme activity has been found in humans. Polyamine catabolism does not produce toxic aldehydes under normal conditions, but inflammation and some pathogens provoke an inducible enzyme, spermine oxidase, which only breaks down spermine to produce acrolein, resulting in cytotoxicity and the activation of autophagy. Therefore, spermine oxidase activation reduces spermine concentration and the ratio of spermine to spermidine, a feature recently reported in patients with age-related diseases. Spermine, which is increased by a long-term, continuous high polyamine diet, suppresses aberrant gene methylation and the pro-inflammatory status that progress with age and are strongly associated with the development of several age-related diseases and senescence. Changes in spermine concentration and the spermine/spermidine ratio should be considered as indicators of human health status.